MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS MELALUI PROBLEM-BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA KELAS V - Agustin, Ria Tiara; Rusminati, Susi Hermin; Latifaturrohmah, Nila; Atmawati, Putri; Ristanti, Rahmadita Aulya; Apriliani, Ria; Indahyani, Vinny; Sastro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is one of the essential competencies that need to be developed among elementary school students, particularly in mathematics learning, which requires the ability to analyze and solve problems. Observation results indicated that the critical thinking skills of fifth-grade students remained low because the learning process was teacher-centered and insufficiently engaged students in solving real-world problems. This study aimed to improve students’ critical thinking skills by implementing a contextual Problem-Based Learning (PBL) model. The study employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The participants were fifth-grade elementary school students. The findings revealed that implementing contextual Problem-Based Learning effectively improved students’ critical thinking skills. The percentage of students achieving learning mastery increased from 43.3% in Cycle I to 86.7% in Cycle II, representing an improvement of 43.4 percentage points. This improvement was supported by the use of more contextual problems, more structured guidance for discussion, and more effective teacher facilitation throughout the learning process. In addition, students demonstrated positive changes in discussion participation, problem analysis skills, and the ability to provide logical reasoning. Therefore, contextual Problem-Based Learning can serve as an effective instructional alternative for improving elementary school students’ critical thinking skills in mathematics learning. Keywords: Problem-Based Learning (PBL), contextual problems, critical thinking skills ABSTRAK Kemampuan berpikir kritis merupakan salah satu kompetensi penting yang perlu dikembangkan pada siswa sekolah dasar, khususnya dalam pembelajaran matematika yang menuntut kemampuan menganalisis dan memecahkan masalah. Hasil observasi menunjukkan bahwa kemampuan berpikir kritis siswa kelas V masih rendah karena proses pembelajaran cenderung berpusat pada guru dan kurang melibatkan siswa dalam pemecahan masalah nyata. Penelitian ini bertujuan untuk meningkatkan kemampuan berpikir kritis siswa melalui penerapan model Problem Based Learning (PBL) berbasis masalah kontekstual. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas V sekolah dasar. Hasil penelitian menunjukkan bahwa penerapan model PBL berbasis masalah kontekstual efektif dalam meningkatkan kemampuan berpikir kritis siswa. Persentase ketuntasan belajar meningkat dari 43,3% pada Siklus I menjadi 86,7% pada Siklus II dengan peningkatan sebesar 43,4%. Peningkatan tersebut didukung oleh penggunaan masalah yang lebih kontekstual, arahan diskusi yang lebih terstruktur, serta pendampingan guru yang lebih optimal selama proses pembelajaran. Selain itu, siswa menunjukkan perubahan positif dalam keaktifan berdiskusi, kemampuan menganalisis masalah, dan menyampaikan alasan secara logis. Dengan demikian, model PBL berbasis masalah kontekstual dapat menjadi alternatif pembelajaran yang efektif untuk meningkatkan kemampuan berpikir kritis siswa sekolah dasar pada pembelajaran matematika. Kata kunci: Problem Based Learning (PBL), masalah kontekstual, kemampuan berpikir kritis